Analysis of Maharah Qira'ah Learning Based on E-Learning for Fourth Siemester Students of the PBA Study Program in the Era of the Covid-19 Pandemc: Analisis Pembelajaran Maharah Qira'ah Berbasis E-Learning Mahasiswa Semester IV Prodi PBA di Era Pandemi Covid-19 - Janah, Roikhatul; Anwar, Najih (Universitas Muhammadiyah Sidoarjo, 2023)
The purpose of this research to describe the learning process of maharah qira'ah based on e-learning for fourth semester students of PBA UMSIDA study program in the era of the covid-19 pandemic. This study uses a qualitative research approach. Data collection techniques used are interviews, observation and documentation. The data analysis technique is data reduction, data display and verification. The results of this study indicate that: planning for e-learning-based maharah qira'ah includes: socialization activities, providing training and guidelines, preparing learning materials, Semester Learning Plans (RPS), and filling in e-learning. The implementation of learning uses the reading method. The learning evaluation includes: assignment, UTS, UAS and individual evaluation. Supporting factors: the use of supporting applications, flexible e-learning characters, UMSIDA wifi facilities, quotas from UMSIDA and the government and the presence of electronic devices. Inhibiting factors: lack of lecturer supervision, less stable internet network, lack of internet quota, lack of interaction between lecturers and students, unclear and detailed explanations, lack of student understanding, limited time and student laziness.